8x-(2x+6)=4x+18

Simple and best practice solution for 8x-(2x+6)=4x+18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8x-(2x+6)=4x+18 equation:


Simplifying
8x + -1(2x + 6) = 4x + 18

Reorder the terms:
8x + -1(6 + 2x) = 4x + 18
8x + (6 * -1 + 2x * -1) = 4x + 18
8x + (-6 + -2x) = 4x + 18

Reorder the terms:
-6 + 8x + -2x = 4x + 18

Combine like terms: 8x + -2x = 6x
-6 + 6x = 4x + 18

Reorder the terms:
-6 + 6x = 18 + 4x

Solving
-6 + 6x = 18 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-6 + 6x + -4x = 18 + 4x + -4x

Combine like terms: 6x + -4x = 2x
-6 + 2x = 18 + 4x + -4x

Combine like terms: 4x + -4x = 0
-6 + 2x = 18 + 0
-6 + 2x = 18

Add '6' to each side of the equation.
-6 + 6 + 2x = 18 + 6

Combine like terms: -6 + 6 = 0
0 + 2x = 18 + 6
2x = 18 + 6

Combine like terms: 18 + 6 = 24
2x = 24

Divide each side by '2'.
x = 12

Simplifying
x = 12

See similar equations:

| -(2x+4y)= | | -32=5u-7 | | 19+4n=1-5n | | 4.2x^4y^14/0.6x^9y^5 | | u+4=6 | | -5x-9=-5x+9 | | -3.5+-6y=7+-6y | | (-4x+6y)-(2x+4y)= | | 12x-30=7x+50 | | 4x^2+16x=-336 | | 5lnx+2ln= | | (w-59)/5=6 | | 4x^4=2x^8 | | w-59/5=6 | | 8x-3(2x+6)= | | (4x+6y)-(2x+4y)= | | -5w-14=-7x | | 9d-5(4-3d)= | | 22-5(x+10)=13 | | 1/10x-12=-42 | | 6(k-8)-(5k+6)=-9 | | 4x+7=53-8x | | -5+6=x+12 | | 81a^2-121p^2= | | -4x+85=30 | | x^3-24x+14=0 | | 2W+2L=210 | | -3x=16-5 | | 6(x-1)=(9x-4) | | 6p+pq+5pr= | | 6(2-y)=10 | | a+25=-100 |

Equations solver categories